The Importance of Regulating Plastic Marine Pollution for the Protection of Indonesian Marine Environment - Ulya Yasmine Prisandani; Adzhana Luthfia Amanda (Yuridika, 2019)
The ocean and its marine resources play an important role in providing sources of livelihood to the Indonesian people. Indonesia is currently dealing with a major plastic waste problem, and this, in turn, also impacts the marine environment since the plastic waste ends up in the ocean. The issue of marine pollution is regulated under international conventions such as the MARPOL and UNCLOS, though none is specifically addressing marine plastic waste. Moreover, Indonesia has enacted several regulations to manage marine plastic waste, including Presidential Regulation Number 83 of 2018 on Marine Waste Management, and Indonesian citizens have taken an active role in reducing plastic waste. However, stricter and more specific regulations are needed as guidelines for the long-term strategy in handling marine plastic pollution in Indonesia, and proper analysis on the impact of such regulation towards the stakeholders and affected parties would be needed.